Fabrication of fiber grating by phase mask and its sensing application - Tahir, B.A; Ali, Jalil B; Rahman, R.A (2006)
This paper reports an investigation of a fabricated fiber grating device characteristics and its applications, using a phase mask writing technique. The phase mask technique used for writing fiber gratings has the advantages over the traditional holographic method because of its simpler writing setup and more reproducible characteristics. Specifically, the utilization of phase mask relaxes the strict requirement on the coherence of a UV light source. On the other hand, to photo induce an index change in the fiber core, light absorption must somehow occur. Alkins measured the absorption spectrum in a standard germanium doped mono mode telecommunication fiber to the wavelength as short as 200 nm. The results show that a light source in the UV spectral region 228 to 253 nm is most effective in photo inducing refractive index changes in such optical fibers. Therefore, we used a KrF excimer laser with wavelength âˆ¼248 nm as light source, and applied the phase mask technique to writing fiber grating. This method has the significant advantage for its much less relaxed requirement on the spatial coherence of exposure light source. The device (i-e grating) characteristics especially, in sensing application, were investigated. In addition, the possibility of using such device as a temperature and strain sensors is also discussed in detail.